PEDAGANG KAKI LIMAâ€ AND IPMLENTATION OF NO 8 REGULATION IN PROBOLINGGO CITY - Prabowo, Hadi (Universitas Dharmawangsa Medan, 2020)
This paper uses pick-title Implementation Regional Regulation No. 8 of2011 Concerning the Development and Structuring Street Vendors: Studyon the Civil Service Unit Kota Probolinggo. There are two questions inthis paper, first, How Probolinggo Implementation Regional RegulationNo. 8 of 2011 Concerning the Development and Structuring Street Vendorsin Kota Probolinggo? Secondly, What are the factors that support andimplementation menghambatdalam Probolinggo Regional Regulation No.8 of 2011 Concerning the Development and Structuring Street Vendors inKota Probolinggo ?. This paper menggnakan qualitative research methodusing descriptive approach of this paper is the first aim of this paper, Todescribe and analyze the implementation of Probolinggo City RegionalRegulation No. 8 of 2011 Concerning the Development and StructuringStreet Vendors. Secondly, to describe and analyze the factors that supportand implementation menghambatdalam Probolinggo Regional RegulationNo. 8 of 2011 Concerning the Development and Structuring Street Vendorsin Kota Probolinggo.